Efficient and reliable screening of anti‐obesity agents on a micro‐cell pattern chip. Issue 10 (8th February 2016) - Kim, Gi Yong; Jeong, Heon‐Ho; Yeom, Su‐Jin; Lee, Chang‐Soo; Roh, Changhyun
Abstract: BACKGROUND: Obesity is a growing global problem and an efficient screening method to discover anti‐obesity agents on a simple platform is needed. Polydimethylsiloxane (PDMS)‐based micro‐cell chips are widely applied to cell studies because of their non‐toxicity and biocompatibility. RESULTS: 3T3‐L1 cells were cultured on a micro‐cell pattern chip. After 6 days, we successfully observed adipocyte differentiation in 3T3‐L1 cells within the micro‐cell pattern chip. Next, 3T3‐L1 cells on the micro‐cell patterned chip were then treated under various concentrations of glycitein and 7, 3′, 4′‐trihydrxyisoflavone (0.2, 0.5 and 1.0 µmol L −1 ) for 10 days. Glycitein and 7, 3′, 4′‐trihydrxyisoflavone exhibited a fat inhibitory capacity of higher than 36% and 44% at 1.0 µmol L −1 in 3T3‐L1 adipocytes, suggesting anti‐obesity activity. It was demonstrated that this platform can be used for real‐time monitoring of cell growth and differentiation in live cell‐based lipid droplets inhibition activity. CONCLUSION: A micro‐cell pattern chip was made using PDMS microstamps through micro‐molding for an efficient, rapid, and reliable cell selective patterning of 3T3‐L1 cells differentiation. The present work provides a proof‐of‐principle demonstration of the direct qualitative and quantitative analysis of adipocyte differentiation through a simple microscopic observation of Oil Red O staining for lipid droplets in cell array patterning. PDMS based micro‐cell pattern chips can be used for the screening of anti‐obesity agents such as glycitein and 7, 3′, 4′‐trihydrxyisoflavone. Furthermore, it is expected that micro‐cell pattern chip technology could be applied to the development of novel bioactive compounds. © 2015 Society of Chemical Industry